Tevez

Solo disponible en BuenasTareas
  • Páginas : 2 (306 palabras )
  • Descarga(s) : 4
  • Publicado : 24 de mayo de 2010
Leer documento completo
Vista previa del texto
1.- E)

y = 4

x + y =
xy

x + 4
4x

2.- B)

f(x) = 3mx + 5 g(x)= (x + 1)2 donde f(1) y g(2)

f(1)= 3m∙1 + 5 = g(2)= (2+1) 2

3m + 5 = (3)2
3m + 5= 9
3m = 9 – 5
3m = 4 /:3
M = 4
3

3.- A)

10º

[pic]

4.- E)

53x + 54x + 52x = 52x (5x + 52x + 1) = 5x
52x + 5x + 53x 5x (5x+ 1 + 52x)

5.- D)

P (x) = 6
D1 = 1,2,3,4,5,6, D2 = 1,2,3,4,5,6,

(1,5), (3,3), (4,2), (5,1), (6,0), (0,6), (2,4) = 7/36

6.- E)

(5a + 5b) = 5 (a + b)= 5
(a + b) (a + b)

7.- A)

8.- C)

2n-1 + 2n =
2n (2-1 + 1)
2n (1 + 1)
2
2n (3)
2
2n ∙ 3
2
2n-1 ∙ 3

9.- B)
85º

10.- A)

A= (a + 2b)2
A = a2 – 4ab + 4b2

11.-

12.- C)

13.-

14.- B)

x (2k – 1) = 3 (2k – 1) ∙ ( 1 ) = -1k + 1

y = x (2k – 1) – 3 2k - 1 = -1
k+1 k + 1

2k = -1 + 1
k+1(k + 1)

2k = -(k + 1) + 1
k+1 (k + 1)

2k = -(k+1) + 1

2k = -k – 1 -+ 1

3k = 0

K = 0
15.-

16.-

17.- E)

A (-2,1) B(-4,3)

___
AB∙ M (x1 + x2 , y1 + y2)
2. 2

M = (-2 – 4 , 1 + 3)
2 2

M = y2 – y1 = 3 – 1 = 2 = 2 = -1
x2– x1 -4 – -2 -4 + 2 -2

___
AB = √( x2 – x1)2 + (y2 – y1)2
___
AB = √(-4 – -2)2 + (3-1)2
___
AB = √(-2)2 + (2)2 = √4 + 4 = √8

18.- B)x2 – y2 : (x + y)
xy xy

(x + y)(x – y) : (x + y)
xy xy

(x + y)(x – y) ∙ xy
xy (x + y)

(x – y)
tracking img